Two-choice discrimination learning in African elephants (Loxodonta africana) - Hyatt, Charles (Pachyderm, 2013)
A study of two-choice discrimination learning across 22 pattern pairs was conducted with three African elephants (Loxodonta africana) at the Atlanta/Fulton County Zoo with rates of acquisition and retention observed to be similar to those earlier reported for the Asian species (Elephas maximus). A significant difference was found in trials to criterion for the second half of the stimulus pairs compared with the first, indicating potential development of the learning set; after seven months with no exposure to the pattern problems, one of the subjects correctly selected the appropriate pattern on 16 of 20 pairs, and the other subject demonstrated improvement on a computer joystick task. This study extends learning research to the African species and indicates potential for further cognitive skill development. Une étude de l’apprentissage de discrimination de deux-choix parmi 22 paires de motifs s’est menée avec trois éléphants africains (Loxodonta africana) au zoo d’Atlanta/Fulton County où les niveaux d’apprentissage et mémoire se ressemblaient à ceux que Rensch (1957) a présenté pour l’espèce asiatique (Elephas maximus). Une différence considérable s’est trouvée dans les chemins de critères pour la deuxième moitié des paires stimulantes par comparaison à la première, ce qui indique le développement possible de l’ensemble de connaissance ; et après sept mois sans exposition aux problèmes, un des sujets a sélectionné correctement le motif approprié avec 16 des 20 paires, et l’autre sujet a démontré de l’amélioration sur une tâche avec un joystick de l’ordinateur. Cette étude étend la recherche de connaissance à l’espèce africaine et indique la possibilité du développement plus profondément des compétences cognitives.